2021
DOI: 10.21203/rs.3.rs-847473/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determination of representative elementary volume (REV) for jointed rock masses exhibiting scale-dependent behavior: A numerical investigation

Abstract: Representative elementary volume (REV) is defined as the usual size of a rock mass structure beyond which its mechanical properties are homogenous and isotropic, and its behavior can be modeled using the equivalent continuum approach. Determination of REV is a complex problem in rock engineering due to its definition ambiguity and application area. This study is one of the first attempts to define a REV for jointed rock masses using the equivalent continuum approach. It is aimed to numerically search a ratio b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…However, the capacity to accurately estimate the hydraulic properties of fractures is hindered by complex influencing factors such as stress conditions (Gale and Raven 1980;Raven and Gale 1985;Yeo et al 1998;Olsson and Barton 2001;Baghbanan and Jing 2008;Rutqvist 2014;, geometric properties (e.g., roughness, aperture dimensions), and fracture stiffness (Zimmerman and Bodvarsson 1996;Konzuk and Kueper 2004;Li et al 2020;He et al 2021). In addition, a number of scholars have reported that the hydraulic properties of fractured rock masses are size-dependent (Bear 1972(Bear , 1979Azizmohammadi and Sedaghat 2020;Han et al 2021;Sari 2021;Ghanbarian 2022;Yu et al 2022), which further compounds the difficulty in estimating representative hydraulic properties. Thus, another important requirement is to establish the relationships between fracture sizes and hydraulic properties (Witherspoon et al 1979;Min et al 2004;Baghbanan and Jing 2007;Sari 2021;Sawayama 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the capacity to accurately estimate the hydraulic properties of fractures is hindered by complex influencing factors such as stress conditions (Gale and Raven 1980;Raven and Gale 1985;Yeo et al 1998;Olsson and Barton 2001;Baghbanan and Jing 2008;Rutqvist 2014;, geometric properties (e.g., roughness, aperture dimensions), and fracture stiffness (Zimmerman and Bodvarsson 1996;Konzuk and Kueper 2004;Li et al 2020;He et al 2021). In addition, a number of scholars have reported that the hydraulic properties of fractured rock masses are size-dependent (Bear 1972(Bear , 1979Azizmohammadi and Sedaghat 2020;Han et al 2021;Sari 2021;Ghanbarian 2022;Yu et al 2022), which further compounds the difficulty in estimating representative hydraulic properties. Thus, another important requirement is to establish the relationships between fracture sizes and hydraulic properties (Witherspoon et al 1979;Min et al 2004;Baghbanan and Jing 2007;Sari 2021;Sawayama 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a number of scholars have reported that the hydraulic properties of fractured rock masses are size-dependent (Bear 1972(Bear , 1979Azizmohammadi and Sedaghat 2020;Han et al 2021;Sari 2021;Ghanbarian 2022;Yu et al 2022), which further compounds the difficulty in estimating representative hydraulic properties. Thus, another important requirement is to establish the relationships between fracture sizes and hydraulic properties (Witherspoon et al 1979;Min et al 2004;Baghbanan and Jing 2007;Sari 2021;Sawayama 2021).…”
Section: Introductionmentioning
confidence: 99%